School Principals’ Strategic Leadership in Implementing Teacherpreneurship in the Digital Era: A Case Study in Primary Schools in Aceh Tamiang District, Indonesia - Rosydha Tanjung; Yusrizal Yusrizal; Munawar Munawar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study investigates the strategic leadership of school principals in executing teacherpreneurship within the digital age in primary schools in Aceh Tamiang District, Indonesia. Teacherpreneurship, which merges teaching expertise with entrepreneurial skills, is vital for enhancing educational innovation, advancing digital literacy, and cultivating teacher creativity. The implementation of teacherpreneurship at the primary level is constrained by poor digital competence, insufficient infrastructure, and lack institutional support, notwithstanding its significance. This research utilized a qualitative case study methodology across two primary schools, incorporating interviews, observations, and document analysis to investigate principals' practices in the creation, implementation, and evaluation of teacherpreneurship programs. The findings reveal that principals' strategies comprise three primary components: (1) strategic formulation, which includes the design of innovation-driven programs and the assessment of teacher capacity needs; (2) strategy implementation, encompassing collaborative leadership, professional development initiatives, digital innovation facilitation, and stakeholder engagement; and (3) strategy evaluation, centred on performance monitoring, barrier identification, and the refinement of innovation programs. The research suggests that teacherpreneurship can substantially improve educational quality when bolstered by visionary leadership, sufficient capacity-building, and digital learning infrastructure. Recommendations encompass enhancing systematic digital training, cultivating innovative ecosystems, and incorporating teacherpreneurship into school development strategies.